Vowel and consonant replacements in the spoken french of ijebu undergraduate french learners in selected universities in south west of Nigeria (2015)
Substitution is a phonological process in language. Existing studies have examined deletion in several languages and dialects with less attention paid to the spoken French of Ijebu Undergraduates. This article therefore examined substitution as a dominant phenomenon in the spoken French of thirty-four Ijebu Undergraduate French Learners (IUFLs) in Selected Universities in South West of Nigeria with a view to establishing the dominance of substitution in the spoken French of IUFLs. The data collection was through tape-recording of participants’ production of 30 sentences containing both French vowel and consonant sounds. The results revealed inappropriate replacement of vowel and consonant in the medial and final positions in the spoken French of IUFLs.